Exploring intersections of age, gender, immigration, ethnicity, and widowhood among older Chinese immigrants in Canada - Wang, Qianyun; Walsh, Christine A.; Tong, Hongmei (My University, 2023)
The population of older adults in Canadian society is aging and becoming more ethnically diverse. Some scholars have explored the lived experiences of older immigrants in Western societies; however, studies on widowhood experiences among older immigrants are extremely limited. By adopting an intersectionality framework, this study seeks to address this gap by examining the influences of age, gender, immigrant status, and ethnicity on the lived experience of widowed older Chinese immigrants in Calgary, Canada. Data were collected from twelve in-depth qualitative interviews and thematically analyzed. Older Chinese immigrants’ widowhood experiences were located within intersections of multiple identities. Findings suggest that an intersectionality perspective could be used to better inform the development of social work practice and policy-making for older immigrants.
Keywords: widowhood; older adults; Chinese immigrants; lived experience; spousal bereavement; intersectionality